CapiPy: python-based GUI-application to assist in protein immobilization - Roura Padrosa, David; Marchini, Valentina; Paradisi, Francesca (Bioinformatics (Oxford, England), 2021)
Abstract Summary Protein immobilization, while widespread to unlock enzyme potential in biocatalysis, remains tied to a trial an error approach. Nonetheless, several databases and computational methods have been developed for protein characterization and their study. CapiPy is a user-friendly application for protein model creation and subsequent analysis with a special focus on the ease of use and interpretation of the results to help the users to make an informed decision on the immobilization approach which should be ideal for a protein of interest. The package has been tested with three separate random sets of 150 protein sequences from Uniprot with more than a 70% overall success rate (see Supplementary information and Supplementary Dataset). Availability and implementation The package is free to use under the GNU General Public License v3.0. All necessary files can be downloaded from https://github.com/drou0302/CapiPy or https://pypi.org/project/CapiPy/. All external requirements are also freely available, with some restrictions for non-academic users. Supplementary information Supplementary data are available at Bioinformatics online.